Successful and Unsuccessful Collaborative Processes in Strangers and Couples Performing Prospective Memory Tasks. Issue 8 (17th November 2019) - Browning, Catherine A.; Harris, Celia B.; Van Bergen, Penny
ABSTRACT: Prospective memory (PM) performance suffers when individuals collaborate, consistent with findings of "collaborative inhibition" in episodic recall. However, prior research indicates strong individual differences, such that some collaborative groups are more effective than others. To identify successful and unsuccessful collaborative processes, we examined dialogue of 20 stranger dyads and intimate couples who worked together to complete an interactive PM task, "Virtual Week." Ten were the highest-performing dyads, and 10 were the lowest-performing dyads. We coded each transcript of their dialogue during the task for cognitive processes, social processes, and generalized conversational skills. A Principal Components Analysis indicated that processes clustered into four factors, with some processes (e.g., task division, monitoring, sociability) being beneficial for both couples and stranger dyads, and others (e.g., demands, critical dialogue) being detrimental for couples only. We conclude that the best strategies to enhance collaborative PM might depend on who is collaborating.